Pengaturan Hukum Gugatan Ganti Rugi Dan Restitusi Terhadap Korban Tindak Pidana Yang Dilakukan Korporasi - Yudha, Fajar Tri; Lubis, Mhd Teguh Syuhada (Universitas Muhammadiyah Sumatera Utara, 2024)
Law and justice are so closely related in everyday life, that it makes no sense to talk about law without being based on justice, because in essence the law that provides justice to society actually becomes a boomerang, especially for people who are victims of criminal acts, this is of course considered very detrimental to victims, the condition of law enforcement in Indonesia is considered very critical in view of the judicial process which is less favorable for victims of criminal acts and in practice it is infiltrated by the hegemony of the judicial mafia. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. Enforcement of national criminal law (both the Criminal Code and the Criminal Procedure Code) must be carried out in accordance with the contents of the provisions of the national criminal law which have been strictly regulated without taking into account the position and interests of the victim. It turns out that until now it has only been a routine routine but without meaning when it comes to dealing with the importance of protection. crime victim law. The mechanism for summoning and examining administrators who are used as witnesses, suspects or defendants still refers to the provisions that are clearly regulated in the Criminal Procedure Code. This is clearly illustrated in the provisions of Article 18 of the Supreme Court Regulations on Corporations which states as follows: The summons and examination of Management who are proposed as witnesses, suspects and/or defendants is carried out in accordance with the Criminal Procedure Code (KUHAP) and statutory regulations. others that apply.